Remote determinations on fumarole outlet temperatures in an eruptive volcano. Issue 22 (26th November 2016) - Tsunogai, Urumu; Cheng, Lin; Ito, Masanori; Komatsu, Daisuke D.; Nakagawa, Fumiko; Shinohara, Hiroshi
Abstract: Direct measurement of the fumarole outlet temperature in active volcanoes is impractical. Therefore, we used an aircraft to sample H2 in the volcanic plume ejected from Sakurajima volcano to remotely estimate the highest fumarolic temperatures of the volcano based on hydrogen isotopic fractionation between H2 and magmatic H2 O. We successfully estimated that the δD of the fumarolic H2 in September and December 2014 was −135 ± 13‰ and −113 ± 11‰, respectively, and that the corresponding highest outlet temperatures were 1050 ± 120°C and 1199 ± 139°C. Although the temperatures were higher than those determined by using infrared remote sensing, we concluded that they are more reliable estimates of the highest fumarole outlet temperatures. Combined with plume sampling by using aircraft, remote temperature sensing based on the δD of H2 in volcanic plumes can be widely applied to active volcanoes to determine the highest fumarole outlet temperatures. Key Points: We remotely determined the outlet temperature of fumaroles in Sakurajima volcano based on isotopes in a volcanic plume The highest outlet temperature was comparable to the temperature of the magma reservoir The present method is the only option available to constrain temperatures of inaccessible fumaroles remotely